Magneto thermoelectric power in heavily doped quantized structures - Ghatak, Kamakhya Prasad 1953- (Series on the foundations of natural science and technology, 2016)
"This pioneering monograph solely deals with the Magneto Thermoelectric Power (MTP) in Heavily Doped (HD) Quantized Structures. The materials considered range from HD quantum confined nonlinear optical materials to HgTe/CdTe HD superlattices with graded interfaces and HD effective mass superlattices under magnetic quantization. An important concept of the measurement of the band gap in HD optoelectronic materials in the presence of external photo-excitation has been discussed in this perspective. The influences of magnetic quantization, crossed electric and quantizing fields, the intense electric field on the TPM in HD semiconductors and superlattices are also discussed. This book contains 200 open research problems which form the integral part of the text and are useful for both PhD aspirants and researchers in the various fields for which this particular series is dedicated"...